2017
DOI: 10.1097/opx.0000000000001035
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Keratoconus-Specific Questionnaire Using Rasch Analysis

Abstract: The 29-item KORQ was a psychometrically robust and valid instrument to assess the impact of keratoconus on activity limitation and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 36 publications
5
39
0
2
Order By: Relevance
“…KEPAQ-E ended up consisting of a total of 7 questions, while the KEPAQ-F ended up consisting of a total of 9 questions. Both subscales demonstrate a good behavior, complying with the Rasch model expectations as specified by Khadka et al 6 ( Table 3). For the final version of the KEPAQ, questions in both sub-scales were rearranged from the easiest-toendorse to the hardest-to-endorse items.…”
Section: Final Version Of the Scalesupporting
confidence: 76%
See 1 more Smart Citation
“…KEPAQ-E ended up consisting of a total of 7 questions, while the KEPAQ-F ended up consisting of a total of 9 questions. Both subscales demonstrate a good behavior, complying with the Rasch model expectations as specified by Khadka et al 6 ( Table 3). For the final version of the KEPAQ, questions in both sub-scales were rearranged from the easiest-toendorse to the hardest-to-endorse items.…”
Section: Final Version Of the Scalesupporting
confidence: 76%
“…Nowadays, Keratoconus Outcomes Research Questionnaire (KORQ) is the only questionnaire designed and explicitly validated in patients with keratoconus, developed by Khadka et al 6 and recently evaluated by Kandel et al 7 However, one of the main limitations of this instrument is that it ignores one of the most important elements in the compromise of QoL in patients with keratoconus and the profound emotional effect that the disease has on its daily functioning. Moshos et al 8 have shown that the presence of keratoconus is associated not only with a higher prevalence of clinical depression but also with a greater intensity of it.…”
Section: Introductionmentioning
confidence: 99%
“…Rasch analysis is a widely accepted methodology to develop and validate PROMs including item banks [13,36]. The advantage of Rasch analysis is that it also provides surgical insights into whether an instrument could form a valid scale based on its assessment on a series of psychometric properties [37]. The following Rasch-based psychometric properties were assessed for the item bank [20,38].…”
Section: Psychometric Properties Assessment Using Rasch Analysismentioning
confidence: 99%
“…(AS-20) 10 , Ocular Comfort Index (OCI) 11 , Ocular Surface Disease Index (OSDI) 11 , Brief Impact of Vision Impairment (IVI) questionnaire 12 , and the Keratoconus Outcomes Research Questionnaire (KORQ) 13 , to name but a few. This study describes the application of Rasch analysis to refine the descriptive system for the CAT-QoL instrument.…”
Section: Introductionmentioning
confidence: 99%